Impact of Artificial Intelligence in Provision of New Job Opportunities (International Journal of Engineering and Computer Science, 2023)
The emergence of Artificial Intelligence (AI) has caused a significant shift in different sectors. AI has proved its ability to automate tasks, offer tailored experiences, and revolutionize fields like healthcare, transportation, finance, customer service, education, security, and entertainment. Despite its impressive influence, the impact of AI has raised ethical and privacy concerns surrounding data protection algorithmic bias, and job displacement. It is imperative to acknowledge the pervasive nature of AI and its fundamental change in the way we interact with technology. Therefore, it is crucial to adopt responsible and ethical use of AI to address these concerns. As such, it is important to recognize the need to ensure that AI is utilized that aligns with industry standards and complies with ethical principles. This will provide a solid foundation for developing AI systems that will enhance productivity, efficiency, and innovation while safeguarding privacy and security.